FACTORS THAT INFLUENCE THE ADOPTION OF INTERNET BANKING AMONG HIGHER EDUCATION STUDENTS AT SEKOLAH TINGGI MANAJEMEN TRANSPORTASI TRISAKTI - MARIS AGUNG TRIANDEWO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
This study examines the level of adoption of Internet banking in Indonesia, particularly students of higher education at Sekolah Tinggi Manajemen Transportasi Trisakti. For theoretical framework, Technology Acceptance Model is adopted by using four independent variables. The sampling method was used with a total of 100 respondents, which included students of higher education at Sekolah Tinggi Manajemen Transportasi Trisakti. To collect the data self-administered questionnaire of two parts were used: Demographic and Likert scale multi-item scale for variables under study. Based on the results, there are indications that convenience, perceived credibility, and perceived use-fulness have significant positive influence among students on the intention to adopt internet banking. The findings from this research would be useful for banks in the subject area, particularly for students of higher education at Sekolah Tinggi Manajemen Transportasi Trisakti.